2011
DOI: 10.1002/mnfr.201100251
|View full text |Cite
|
Sign up to set email alerts
|

Boiling peanut Ara h 1 results in the formation of aggregates with reduced allergenicity

Abstract: Ara h 1 aggregates formed by boiling were morphologically distinct from those formed by roasting and had lower allergenic activity. Glycation had no additional effect on Ara h 1 allergenicity compared with heating alone. Taken together with published data on the loss of Ara h 2/6 from boiled peanuts, this supports the hypothesis that boiling reduces the allergenicity of peanuts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 24 publications
6
79
0
Order By: Relevance
“…Baking, roasting, and various forms of food processing are known to affect the antigenicity of peanuts [24,25], and, as a result, profiling processed foods can be problematic if the standards are not identically processed. Fortunately, as there were no indications that the ground cumins (A and B) were processed, the standards used to generate the data in Table 2 should be directly applicable to these two cumin samples.…”
Section: Cumin Profilingmentioning
confidence: 99%
“…Baking, roasting, and various forms of food processing are known to affect the antigenicity of peanuts [24,25], and, as a result, profiling processed foods can be problematic if the standards are not identically processed. Fortunately, as there were no indications that the ground cumins (A and B) were processed, the standards used to generate the data in Table 2 should be directly applicable to these two cumin samples.…”
Section: Cumin Profilingmentioning
confidence: 99%
“…Some method of facilitated transport (e.g. endocytosis) would be likely, especially given the larger size of Ara h 1, and its tendency to aggregate into insoluble complexes, especially when heated [1,10,34,35]. It has been previously demonstrated that soluble molecules are more easily absorbed across the intestinal epithelium compared to larger insoluble aggregates, which are limited to M cell passage [36].…”
Section: Discussionmentioning
confidence: 99%
“…The compound formed by Ara h 1 and Ara h 6 has a strong immunoreactivity when compared with the native allergen (Guillon, Bernard, Drumare, Hazebrouck, & Adel-Patient, 2016). It has also been reported by Blanc et al (2011) that complex branched aggregates of natural Ara h 1 were produced through boiling, and thus caused a relatively decreased sensitivity. Similar to this result, our data showed that rAra h 1 tends to aggregate after 20 min of heating (Figure 4(A,B)).…”
Section: Discussionmentioning
confidence: 90%
“…However, more extreme thermal processing such as roasting at 140°C appeared to enhance IgE-binding capacity of Ara h 1 (Rao et al, 2016). According to Blanc et al (2011), Ara h 1 boiled in the absence or presence of glucose produced aggregates and thus maintained a relatively lower sensitivity. Researchers utilized various thermal methods to treat peanut kernel or a certain allergen and explored the influence of heat treatment on the immunoreactivity, and the results were not consistent with each other.…”
Section: Introductionmentioning
confidence: 99%